2020
DOI: 10.2147/ott.s235533
|View full text |Cite
|
Sign up to set email alerts
|

<p>Tetrandrine Reverses Paclitaxel Resistance in Human Ovarian Cancer via Inducing Apoptosis, Cell Cycle Arrest Through β-Catenin Pathway</p>

Abstract: Background: Paclitaxel (PTX) resistance is a great obstacle for the treatment of ovarian cancer. A previous study indicated that tetrandrine (TET) could induce the apoptosis of ovarian cancer cells. This study aimed to explore the effect of TET in combination with PTX on PTX resistance in ovarian cancer cells. Materials and Methods: CCK-8 assay, flow cytometry and wound healing assays were used to detect the proliferation, apoptosis and migration of PTX-resistant SKOV3 cells (SKOV3/PTX). The expressions of Bax… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
10
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 17 publications
(10 citation statements)
references
References 35 publications
0
10
0
Order By: Relevance
“…Moreover, emerging evidence also suggests that dysregulation of cell cycle signaling cross-cascade is commonly been observed in a broad range of human cancers [ 34 , 35 ]. Especially, relevant co-DEGs were also most striking in cell cycle pathway associated highly with the tumorigenesis and progression of ovary cancer [ 36 , 37 ].…”
Section: Discussionmentioning
confidence: 99%
“…Moreover, emerging evidence also suggests that dysregulation of cell cycle signaling cross-cascade is commonly been observed in a broad range of human cancers [ 34 , 35 ]. Especially, relevant co-DEGs were also most striking in cell cycle pathway associated highly with the tumorigenesis and progression of ovary cancer [ 36 , 37 ].…”
Section: Discussionmentioning
confidence: 99%
“…Antioxidants are able to attenuate the damaging effects of ROS, and tetrandrine has been suggested to have potential as an antioxidant drug in (47). Studies have shown that tetrandrine induces cytotoxic effects through the induction of apoptosis of many types of human cancer cells in vitro (48,49). The relationship between tetrandrine-and H 2 O 2induced cell death remains underexplored.…”
Section: Discussionmentioning
confidence: 99%
“…Ovarian Cancer (OC) is a global issue representing the fourth most common cancer in the female population, particularly in developed countries [ 115 ]. The poor survival rate is mainly due to the lack of screening methods at the early stages along with the absence of effective treatment options for advanced stages [ 116 ].…”
Section: Ovarian Cancermentioning
confidence: 99%
“…Jiang et al [ 115 ] have demonstrated that tetrandrine (TET) enhances the anti-tumour effect of paclitaxel (PTX) by decreasing c-myc and cyclin D1 and increasing p21 expression, resulting in cell cycle arrest. The pro-apoptotic effects of PTX+TET have also been investigated.…”
Section: Canonical Wnt Pathway and Ocmentioning
confidence: 99%
See 1 more Smart Citation